Correction: Stoll et al. Impact of HLA-B27 and Disease Status on the Gut Microbiome of the Offspring of Ankylosing Spondylitis Patients. Children 2022, 9, 569 - Matthew L. Stoll; Kimberly DeQuattro; Zhixiu Li; Henna Sawhney; Pamela F. Weiss; Peter A. Nigrovic; Tracey B. Wright; Kenneth Schikler; Barbara Edelheit; Casey D. Morrow; John D. Reveille; Matthew A. Brown; et al. (MDPI AG, 2022)
The authors wish to make the following correction to this paper [...]